A critical assessment of the Wilhelmy method in studying lung surfactants. - Barrow, R E (1979)
1. The surface properties of over 250 films of diplamitoyl lecithin (DPL) and Tween 20 on distilled water have been investigated using two different surface balances simultaneously, the Wilhelmy balance, popular in physiological studies, and the Du Nuoy ring method whose readings are independent of contact angle. 2. Using concentrations of DPL ranging from 0.08 to 1.90 microgram cm-2 on a Langmuir trough where the pool area was cycled from 100 to 27.5% of maximum, the Wilhelmy balance registered virtually the same force per wetted perimeter as the ring method for both pure water and Tween 20, but appreciably lower values for DPL over the whole cycle. 3. The above differences can be explained on the basis of a significant (45-70 degrees) contact angle, a surface property also demonstrated photographically and by direct measurement. 4. Contact angle was shown to vary with pool area, a relationship exhibiting hysteresis. 5. This study indicates that the Wilhelmy balance has been an unfortunate choice of instrument for studying DPL films whose surface tensions are appreciably higher than previously estimated.